2016
DOI: 10.1016/j.livsci.2016.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Core body temperature does not cool down with skin surface temperature during recovery at room temperature after acute heat stress exposure

Abstract: Identifying new methods of assessing livestock welfare is a growing area of research. Non-invasive methods such as infrared thermography are valuable for quick and accurate observations and could be utilized to monitor the thermal status of swine without direct contact. The study objective was to determine if infrared thermography could be used as a non-invasive, hands-off approach to accurately monitor the welfare of swine by comparing changes in skin surface temperature (SST), core body temperature (CBT), be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The normal body temperature in resting piglets is about 39.5 °C, in finishing pigs 39.3 °C, in gilts 38.8 °C and in multiparous sows it is about 38.3 °C [ 24 ]. The average skin-surface temperature is about 33.5 °C in pigs kept in a thermoneutral zone [ 25 ].…”
Section: Thermoregulation Behavioural and Physiological Changes Imentioning
confidence: 99%
See 1 more Smart Citation
“…The normal body temperature in resting piglets is about 39.5 °C, in finishing pigs 39.3 °C, in gilts 38.8 °C and in multiparous sows it is about 38.3 °C [ 24 ]. The average skin-surface temperature is about 33.5 °C in pigs kept in a thermoneutral zone [ 25 ].…”
Section: Thermoregulation Behavioural and Physiological Changes Imentioning
confidence: 99%
“…The second phase of acclimatisation was characterised by a gradual decrease and subsequently reached relative constant levels of these parameters [ 26 ]. The acute-stress response was evaluated by Sapkota et al [ 25 ]. The authors showed that after 30 min of exposing pigs to heat load (air temperature of 39.3 °C) the body-core temperature (measured in digestive tract) increased from 38.3 °C (neutral conditions) to 40.3 °C.…”
Section: Thermoregulation Behavioural and Physiological Changes Imentioning
confidence: 99%
“…Rectal temperature measurements, however, require handling, which may disturb the animal, potentially altering its thermal status [ 87 , 88 ]. Additionally, rectal measurements are time-spot measurements, which may limit the acquisition of information for the assessment of animal thermal status [ 54 , 71 , 87 , 89 ]. Several studies have tested alternative measurement techniques to validate indicators used to check body temperature, which can monitor thermal status in a continuous fashion with less invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that the highest correlation was obtained in the front site dominated by the brain which regulates the body temperature via central nervous system (CNS) (Martello et al 2016). However, Sapkota et al (2016) discovered that core body temperature could be estimated by skin surface temperature by IRT was only in the thermoneutral condition. Their study resulted that when animal was recovered from acute heat stress to thermoneutral condition, the skin temperature drastically dropped within 10 min whereas core body temperature still elevated for 30 min.…”
Section: The Accuracy Of Infrared Thermography In Detecting the Core mentioning
confidence: 99%